Evaluation of cardiac function tests in Sudanese adult patients with sickle cell trait (Medical Journal of Indonesia, 2016)
Background: Cardiac dysfunctions have been recognized as a common complication of sickle cell anaemia (SCA), and together with pulmonary disorder accounts for many deaths in these patients. However, sickle cell traits appear clinically normal, although they have genetic abnormality. The aim of this study was to assess the effect of sickle cell trait on cardiac prognostic markers by measuring high density lipoprotein (HDL-C), low density lipoprotein (LDL-C), cardiac creatine kinase (CK-MB), ultra-sensitive C reactive protein (us-CRP), total homocysteine (Hyc), and N-terminal pro-brain natriuretic peptide (NT-pro BNP) tests in adult Sudanese patients with sickle cell trait. Methods: A cross-sectional study was performed in 200 healthy volunteers as a control group and 200 diagnosed patients with sickle cell trait. It was carried out in Khartoum Specialized Hospital, Al-Bayan Hospital, Obayed Clinical Center and Dr. Nadir Specialized Hospital, Sudan between January 2015 and January 2016. All participants were between 20-32 years old. LDL-C, HDL-C, CK-MB, NT-proBNP and hs-CRP concentrations were measured by Hitachi 912 full-automated Chemistry Analyzer (Roche Diagnostics, Germany) as manufacturer procedure, while homocysteine level was measured by ELISA technique using special kit. Results: When compared to control group, the levels of LDL-C, hs-CRP and NT-proBNP revealed significant increase in patients’ sera (p<0.001), while Hyc and CK-MB levels were increased insignificantly in patients with SCT (p=0.069, p=0.054 respectively). On the other hand, comparison to control group, HDL-C showed insignificant reduction in patients (p=0.099). Conclusion: The results suggest that sickle cell trait increased the risk of patient-related complication secondary to cardiac dysfunction.